FRI0375 Clinical characteristics and vitamin D insufficiency in a population of 54 adults with osteogenesis imperfecta. (23rd January 2014) - Payet, J.; Cormier, C.
Abstract : Background: Osteogenesis imperfecta is a rare heritable disorder of connective tissue characterized by bone fragility and fractures occuring with trivial traumatism. It is caused in 90% of cases by mutations in genes encoding the type 1 collagen. Vitamin D insufficiency is defined by 25 OH vitamin D <30 ng/ml and vitamin D deficiency by 25 OH vitamin D <20 ng/ml. It is considered that 40 to 100% of the healthy adult population is insufficient in vitamin D. Objectives: To describe clinical characteristics of a population of 54 adult patients with osteogenesis imperfecta, to establish prevalence of vitamin D deficiency and to analyze bone mineral densities (BMD). Methods: Study design: retrospective, observational study. Patients: adults with osteogenesis imeprfecta coming in day hospital after a recent bone event. Data collection: clinical features (number of fractures, family history, received treatment), 25OH vitamin D level, BMD when feasible. Statistical analyses: descriptive analyses. Results: In all, 54 patients were included in the study. Mean (±SD) age was 39.3 (±11.3) years at the time of inclusion in the study. Among the 54 patients, 16 (39.6%) were men and 26 (48.1%) had family history of osteogenesis imperfecta. Mean (±SD) number of fractures per patient was 30.7 (±30.9). Mean age at the time of last fracture was 33.8 (±14.8) years. Mean level of vitamin D was 21.9 (±11.3) ng/ml. In all, 39 patients (72.2%) had 25 OH vitamin D level <30 ng/ml and 27 patients (50.0%) had a level <20 ng/ml. The Z score was less than -2 DS at one or more site in 34/40 (85.0%) patients. There was no correlation between total number of fracture and BMD. Twenty seven patients (56.2%) had vitamin D supplementation. Twenty seven patients (61.4%) had a history of treatment with bisphosphonates. Patients with vitamin D supplementation were less often insufficient in 25 OH vitamin D (p=0.005). Patients with insufficiency in vitamin D were not different from the population with normal level of vitamin D concerning total number of fractures or recent fracture. Conclusions: In a population of 54 adults with OI, 72.2% had vitamin D insufficiency and 50% had vitamin D deficiency. Juste over half of them had a vitamin D supplementation. Systematic supplementation at adequate doses seems necessary. Disclosure of Interest: None Declared